Transformasi Layanan Publik di Kabupaten Gowa: Penerapan Mal Pelayanan Publik untuk Meningkatkan Efisiensi dan Aksesibilitas - Sari, Inrinofita; Dwi Nurfaisal, Muhammad; Akbar Maulana, Muhammad; Syukri, Ahmad; Wahdaniyah, Nurul (Kybernology : Journal of Government Studies, 2025)
This research aims to analyse the implementation of the Public Service Mall (MPP) in Gowa Regency within the framework of public sector governance, by relating it to governance theories such as New Public Management (NPM), New Public Service (NPS), and New Public Governance (NPG). This research focuses on how MPP is able to improve efficiency, transparency, and accessibility of public services for the community. The research method used is a qualitative method with a descriptive approach. Data was collected through document analysis, official reports, and relevant previous research. Analysis was conducted using data reduction, data presentation, and conclusion drawing techniques to produce an in-depth interpretation of the phenomenon under study. The results show that the MPP in Gowa Regency successfully reflects NPM principles through technology integration and simplification of service processes. In addition, the NPS approach is evident from the government's efforts to involve the community through satisfaction surveys and fair and responsive service delivery. The multi-sector collaboration adopted by the MPP reflects the application of NPG principles in improving the effectiveness and sustainability of governance. However, challenges related to digital literacy and infrastructure still affect service accessibility, especially in remote areas. Research limitations include limited primary data that relies solely on documents and data collection, and ended direct observation of MPP operations in Gowa Regency. The implications of the study include recommendations to improve digital community literacy through education programs and the provision of more equitable technology infrastructure in remote areas. In addition, this study provides guidance for other local governments in adopting agile governance principles to improve the quality of public services through the integration of services and technology.